Comparative information on New South Wales local government councils - New South Wales. Department of Local Government (Bankstown, N.S.W. : NSW Department of Local Government, 1996)
"Comparative performance publication under the new accrual accounting standard, AAS 27 Financial Reporting by Local Governments, which has applied to the financial reports prepared by councils throughout Australia on or after 1 July 1993.... Subsequent publications will contain performance data for each financial year. They will enable each council to compare trends in their key performance indicators and review performance relative to other councils." -- Introduction.
Title from title screen (viewed on 16 February 2010).
Text.
Available via World Wide Web. On 16/2/10 vailable from website of Department of Local Government & Co-operatives: http://www.dlg.nsw.gov.au/dlg/dlghome/dlg_index.asp.
System requirements: Adobe Acrobat Reader to access files in a PDF format.
Selected for archiving
Keywords: Local government -- New South Wales -- Periodicals; Local government -- New South Wales -- Statistics -- Periodicals